KEWAJIBAN MEREDAM EMOSI BAGI SUAMI TERHADAP AKHLAK ISTRI : Analisis Hadis Lā Yafrak Mukminun Mukminatan In Kariha Minhā Khuluqan Radiya Minha Ākhar - Mutammimah, Bidayatul; Nasrulloh (DIRAYAH : Jurnal Ilmu Hadis, 2024)
Mitigating emotions for the husband is the foundation for building a sakinah mawaddah wa rahmah family, by weighing the positive and negative sides of the wife fairly. The purpose of writing this article is to explain the obligation of a husband to suppress his emotions toward his wife's morals. This research method uses a qualitative descriptive approach by deepening the study of the husband's obligation to suppress the emotions of his wife's treatment of him by analyzing the hadith related to him. There are three results in this study, [1] The hadith la yafrak mukminun mukminatan in kariha minha khuluqan radiya minha akhar is an authentic hadith that must be practiced. [2] Emotional damping is included in the process of managing emotions which has a positive relationship with marital satisfaction, so the ability to manage these emotions must always be improved. [3] Improving emotional intelligence is an obligation for husbands who hold the title of head of the family because this can affect the level of patience that is in him so that the husband is not too emotional in dealing with his wife and even dampens his emotions by remembering all the good things that exist in his wife. From this treatment, the husband and wife can build a happy, peaceful, and comfortable family.